Human platelet-derived growth factor A chain is transcriptionally repressed by the Wilms tumor suppressor WT1. - Gashler, A L (1992)
Wilms tumor, an embryonic kidney malignancy, accounts for approximately 6% of all pediatric neoplasms. A gene implicated in the genesis of this tumor, the Wilms tumor suppressor gene (WT1), encodes a zinc-finger DNA-binding protein (WT1) that functions as a transcriptional repressor. In certain Wilms tumors, the platelet-derived growth factor A chain (PDGF-A) is overexpressed; it has therefore been suggested that it may play an autocrine role in development of these neoplasms. Since the PDGF-A promoter contains putative binding sites for WT1, we explored the role of WT1 in regulating A-chain expression. The major PDGF-A promoter activity was localized in transient transfection assays to a region spanning from -643 to + 8 relative to the transcription start site. WT1 bound to several sites in this region of the promoter, as demonstrated by gel-shift analysis and DNase I footprinting, and functioned as a powerful repressor of PDGF-A transcription in vivo. Maximal repression (> 50-fold) of the PDGF-A promoter was dependent on the presence of multiple WT1 binding sites in transient transfection assays. Our observations suggest a mechanism for normal downregulation of a growth factor gene and of an autocrine growth process of import in kidney development and other biological systems.